'They live on in the photos': the ontologies of difference when recognition is given to descendant family and kin concern for, and responsibility toward, Aboriginal ancestors in photographs. Issue 4 (20th October 2021) - Huebner, Sharon; Bradley, John
Abstract : This paper considers the ontologies of relational repatriation, cultural reclamation and reorientation from past to present of ancestor photos by Aboriginal Elders, knowledge holders and their families. It leans into questions about cultural custodianship rights and the renewal of family kinship responsibilities to ancestors and kin, pictorially confined to repository collections of 19th and early 20th Century photographs. It engages with dialectical approaches to heritage reclamation and attends to the dialogic ethics and morals of an intimate social relatedness that does not separate history from meaningful experience, cultural authority from emotions. This paper explores cultural perceptions of identity and belonging animated by descendant family members when experiencing ancestors and kin pictured in photographs. Closely examined are the complexities of these interrelationships and the energetic social and political desire of Elders, knowledge holders, and their families to make something happen as part of contemporary knowledge practices, and for the continuity of collective memory and legacy – knowing the self through remembering ancestors and kin in relationship to country, each other, and the acknowledged power of oral narratives throughout time.